2019
DOI: 10.1021/acs.chemmater.9b03570
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Imine Substitution in Wide-Bandgap Polymer Donor-Induced Efficiency Enhancement in All-Polymer Solar Cells

Abstract: All-polymer solar cells (all-PSCs) are proven to possess outstanding thermal and mechanical stabilities. However, concurrently achieving appropriate phase-separated pattern, efficient charge transportation, and adequate charge transfer between donor and acceptor components is still a challenge, and thus, only a few polymer−polymer bulk heterojunction (BHJ) blends have yielded BHJ device power conversion efficiency (PCE) values of >8%. Generally, polymer backbone substitutions may have a direct influence on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 44 publications
2
53
0
2
Order By: Relevance
“…[ 19 ] In addition, environmentally sensitive asymmetric TTz derivatives can serve as molecular probes for cell imaging and cell membrane voltage sensing. [ 33 ] The excellent electronic and optical properties of TTz‐based materials have enabled them to be studied in a variety of molecular electronic applications such as organic photovoltaics (OPVs), [ 34 ] organic field‐effect transistors (OFETs), [ 35–37 ] organic light‐emitting diodes (OLEDs), [ 38 ] metal‐organic framework/covalent‐organic framework materials, [ 39–42 ] and redox flow batteries. [ 43 ] Herein, multifunctional chromogenic devices (CGDs) (electrochromic, EFC, and photochromic) are demonstrated using extended TTz viologens developed for low cost, non‐toxic, and water‐based hydrogel devices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] In addition, environmentally sensitive asymmetric TTz derivatives can serve as molecular probes for cell imaging and cell membrane voltage sensing. [ 33 ] The excellent electronic and optical properties of TTz‐based materials have enabled them to be studied in a variety of molecular electronic applications such as organic photovoltaics (OPVs), [ 34 ] organic field‐effect transistors (OFETs), [ 35–37 ] organic light‐emitting diodes (OLEDs), [ 38 ] metal‐organic framework/covalent‐organic framework materials, [ 39–42 ] and redox flow batteries. [ 43 ] Herein, multifunctional chromogenic devices (CGDs) (electrochromic, EFC, and photochromic) are demonstrated using extended TTz viologens developed for low cost, non‐toxic, and water‐based hydrogel devices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Generally, to make full use of solar energy in OSCs, different donors, including wide bandgap, medium bandgap, and narrow bandgap (NBG) donor materials, are developed to match well with different acceptors. [ 2 ] Among these donors with different bandgaps, the NBG polymers have some intrinsic characteristics, for instance, the optical absorption of NBG polymers can reach to the near‐infrared (NIR) region, hence, more sunlight photons can be harvested when NBG donors are paired with fullerene derivative acceptors. [ 3 ]…”
Section: Methodsmentioning
confidence: 99%
“…Recently, thiazolothiazole (TTz)-based polymer donors have yielded impressive performance in OSCs owing to its coplanar backbone, wide-bandgap, appropriate FMOs, and large holetransport character. [46][47][48] For example, Zhang and co-workers developed a polymer donor poly [4,8- [5,4-d]thiazole] (PSTZ) with a wide-bandgap of 1.96 eV and deep-lying highest occupied molecular orbital (HOMO) of À 5.44 eV, which has exhibited a high PCE of 11.1 % when mingled with two compatible FREAs (i. e., IDIC and ITIC). [47] In addition, Cao et al also reported the similar polymer donor PBDT-TTz to afford high PCE of 8.4 % in all-PSC devices when blended with benchmark N2200.…”
Section: Introductionmentioning
confidence: 99%